The Legal Nature of Decisions of Constitutional Courts of Russia and Foreign Countries and Investigating its Psychological Consequences - Tonkov, Evgeniy E. (2020)
The authors, on the basis of the importance of the activities of constitutional courts in the system of separation of powers in most countries, propose a comparative legal analysis of the normative and legal acts governing the procedure for the adoption and legal nature of decisions of these bodies. On the basis of the study of the legal consolidation of the activities of the constitutional courts, it was concluded that the decisions of the constitutional courts, possessing such characteristics as the possibility of abolishing the legal norm; the final character; the obligation of execution for all state authorities, organizations and citizens; and the moral authority, perform a law-making function, establish rules governing important relations in society and play a special role in ensuring and protecting fundamental human and civil rights and freedoms plays an important role in ensuring and protecting fundamental human and civil rights and freedoms and constitutions of the countries considered in this article.